Characteristics of frond stipe nectaries in two subspecies of Pteridium aquilinum (L.) Kuhn in Poland - Zenkteler, Elżbieta; Ślachetka, Magdalena; Michalak, Kornel M. (Biodiversity: Research and Conservation, 2023)
Although both subspecies of Pteridium aquilinum (subsp. aquilinum and subsp. pinetorum) are widespread in Poland, our knowledge about the occurrence and significance of extrafloral nectaries on frond stipes (petioles) is very limited. Their location on the abaxial stipe surface in pairs at subsequent pinna-bases is often overlooked. The study concerns the morphological/anatomical structure, distribution, and function of the bracken nectaries. Observations of sugar secretions of the nectaries and their local associations with ants indicated a dependence on frond age, seasonality, and environmental factors. The nectaries consist of a single layer of the epidermis with stomata, secretory parenchyma, and ground parenchyma cells lying above the vascular bundles, with a hypodermal sterome composed of fibres. The anatomy of the two examined subspecies revealed a close similarity, despite the morphological differences in size, shape, colour, and secretory activity. This paper provides also a review of published data on the nectaries in P. aquilinum and other fern species.